ANALISIS PENGARUH ROE, EPS, NPM dan MVA TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR GO PUBLIC SEKTOR FOOD DAN BEVERAGES DI BEI TAHUN 2009-2013) - Manurung, Henry Togar; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2015)
The capital market are the activities that deals with public offering, trade effect, a public company which relates to the effect that the issuance, as well as agencies and a profession which relates to the effect. In the capital market, corporation gaining relatively cheap funds, because the company didn’t pay the cost of capital or capital cost can be reduced. Of the securities often be sold in the capital market are stock. On the stocks manufacturing companies go public sector food and beverages there are fluctuations and then there are phenomenon gap between theories and existing reality. The purpose of this research is think about how the influence of Return On Equity (ROE), Earning Per Share (EPS), Net Profit Margin (NPM) dan Market Value Added (MVA) on the stock price in the company manufacturing go public sector food and beverages.Population and samples in this study are all companies listed on the Stock Exchange of the year 2009-2013. The selection of the sample in this study using purposive sampling method with certain criteria. Type of dat is secondary. Data analysis method used is descriptive analysis, the classical assumption (Normality Test, Test Multicollinearity, Autocorrelation test, Heteroskedastitity test), Multiple linear regression analysis, hypotesis testing (F – statistic test, t-statistic test, coefficient of determination test).The results showed that the ROE, EPS, NPM and MVA simultaneously affect the stock price. Partially this research found that ROE have a positive and significant effect on Stock Prices, EPS have a positive and significant effect on Stock Prices, NPM have a negatife and significant effect on Stock Prices, MVA have a positive and significant effect on Stock Prices.